Persistent Low-level Viremia While on Antiretroviral Therapy Is an Independent Risk Factor for Virologic Failure. (16th February 2019) - Joya, Christie; Won, Seung Hyun; Schofield, Christina; Lalani, Tahaniyat; Maves, Ryan C; Kronmann, Karl; Deiss, Robert; Okulicz, Jason; Agan, Brian K; Ganesan, Anuradha
Abstract: Background: Whether persistent low-level viremia (pLLV) predicts virologic failure (VF) is unclear. We used data from the US Military HIV Natural History Study (NHS), to examine the association of pLLV and VF. Methods: NHS subjects who initiated combination antiretroviral therapy (ART) after 1996 were included if they had 2 or more VLs measured with a lower limit of detection of ≤50 copies/mL. VF was defined as a confirmed VL ≥200 copies/mL or any VL >1000 copies/mL. Participants were categorized into mutually exclusive virologic categories: intermittent LLV (iLLV) (VL of 50–199 copies/mL on <25% of measurements), pLLV (VL of 50–199 copies/mL on ≥25% of measurements), high-level viremia (hLV) (VL of 200–1000 copies/mL), and continuous suppression (all VL <50 copies/mL). Cox proportional hazards models were used to evaluate the association between VF and LLV; hazard ratios and 95% confidence interval (CI) are presented. Results: Two thousand six subjects (median age 29.2 years, 93% male, 41% black) were included; 383 subjects (19%) experienced VF. After adjusting for demographics, VL, CD4 counts, ART regimen, prior use of mono or dual antiretrovirals, and time to ART start, pLLV (3.46 [2.42–4.93]), and hLV (2.29 [1.78–2.96]) were associated with VF. Other factors associated with VF include black ethnicity (1.33 [1.06–1.68]) and antiretroviral use prior to ART (1.79 [1.34–2.38]). Older age at ART initiation (0.71 [0.61–0.82]) and non-nucleoside reverse transcriptase inhibitor (0.68 [0.51–0.90]) or integrase strand transfer inhibitor use (0.26 [0.13–0.53]) were protective. Conclusion: Our data add to the body of evidence that suggests persistent LLV is associated with deleterious virologic consequences. Abstract : Results of a large systematic analysis of subjects infected with human immunodeficiency virus with persistent low-level viremia (pLLV) indicate that pLLV is an independent predictor of virologic failure; presence of pLLV should not be merely ascribed to laboratory variation and needs investigation.